Spectrum of Adverse Event Following COVID-19 Immunization in High Altitude, Nepal (One Health Journal of Nepal, 2024)
Introduction: Nepal started vaccinating frontline workers against COVID-19, in January 2021. Side effects of the vaccine are still unknown in high-altitude regions. Poor surveillance and the lack of health workers in remote places to take care of people in case of vaccination could prove to be a challenge in the drive, in high altitudes like Humla district, Nepal. High-altitude regions are harder to access and mobilization of vaccines and manpower is strenuous due to harsh weather conditions and complex geography. We aimed to study the spectrum of Adverse Events Following COVID-19 Immunization among the front liners of the Humla district.Methods: This is a cross-sectional study conducted in Humla district, Nepal. COVID-19 Immunization vaccine recipients were contacted through a phone call within 5 days of vaccination to record the adverse effects. Patterns and distribution of adverse effects were analyzed in high-altitude settings. Ethical approval was taken from the Nepal Health Research Council.Results: Of the total respondents, 84.1% (95% C.I: 80.9 to 86.9) had shown symptoms after vaccination. The average time for the appearance of symptoms was 1.27 ± 0.60 days. For systemic effects, tenderness was the side effect seen after vaccination (63.8%) followed by other side effects like pain (58.5%), Pyrexia (37.4%), Chills (29.8%), Myalgia (28.9%), and Malaise (15.2%) while for localized effects, the symptoms such as Arthralgia (16.6%) and Bruising (16.1%) were the most common effects.Conclusions: Serious and life-ife-threatening adverse effects following immunization were not seen in our study site which was at an altitude of 2500 meters and above. Our study shows a similar type of side effect pattern as that of the lower altitude regions.